Strategi Pemberdayaan Kelompok Usaha Karang Biru di Pesisir Labuhan Lalar sebagai Upaya Pengembangan Ekonomi Pesisir Berkelanjutan di Kabupaten Sumbawa Barat - Rizka Donny Agung Saputra; Lidiawati; Jamiatul Aulia; Dewi Seprianingsih; SAHRATULLAH, SAHRATULLAH (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
This study aims to analyze and implement strategies for empowering the "Karang Biru" business group located in the coastal area of Labuhan Lalar, Sumbawa Barat. The group faces challenges in optimizing their economic potential while maintaining environmental sustainability. Through community engagement and sustainable development practices, this empowerment program seeks to enhance their economic independence while promoting coastal resource conservation. The focus areas include capacity building, market access, and sustainable resource management. This initiative is expected to serve as a model for other coastal communities in Indonesia.